Avaliação de rizobactérias Streptomyces para o controle do fitopatógeno Sclerotinia sclerotiorum - Missau, Luiza Zardin (2022)
Brazil is the largest producer and exporter in the world of one of the main world commodities – soybean. There are several factors that can impair the yield potential of soybeans, among which it is possible to highlight the damage caused by fungal diseases, such as white white mold (Sclerotinia sclerotiorum). This pathogen can cause losses of up to 80% in the productivity of a crop. The management of white mold must be carried out through the adoption of several control measures aimed at reducing its incidence rate. In this way, biological control comes as an alternative to the use of agrochemicals for maintaining the ecological balance of the environment. The genus Streptomyces, belongs to the Actinobacteria phylum, and has great potential as a biological control agent for phytopathogens due to the production of bioactive compounds from its secondary metabolism, resulting in molecules with chemical diversity and varied biological action, such as antibiotics, anti-inflammatory drugs, in addition to production of vitamins and enzymes, which interfere with the fungal cell cycle. The aim of this work was to evaluate four isolates (CLV16, CLV100, CLV103 and CLV115) of the genus Streptomyces to control the fungus S. sclerotiorum. The results show that the isolates are efficient in inhibiting the growth of the phytopathogen, with a reduction in growth of 60% (CLV16), 53.2% (CLV103), 30.4% (CLV100) and 31.7% (CLV115). CLV results cannot be attributed to the presence of organic volatiles (P=0.18). The growth of the fungus S. sclerotiorum was not inhibited by exudates extracted from liquid and solid cultures of Streptomyces. The absence of antimicrobial activity in CLV exudates suggests that the inhibitors may be unstable and degraded in the process of obtaining semi-purified fractions. Analysis of exudates, CLVs cultured in solid medium indicate that CLV16 had the highest levels of soluble proteins. No proteins were identified in CLV103. The CLVs are stronger when cultivated in solid medium, highlighting the CLV16 as the most productive. CLVs produce phenazines that recognized antimicrobial capacity. However, there was no control. CLVs produce indole compounds related to auxin synthesis (IAA). ICA (Indole-3- carboxylic acid) was produced under all culture conditions (liquid and solid) and by all isolates. The isolate CLV103 showed the lowest levels of synthesis of indole compounds in the liquid medium. It was not possible to determine the mechanism used by CLVs in the inhibition of S. scleotiorum. It is suggested that this may occur indirectly, through competition for nutrients. Possibly due to a synthesis of siderophores. Additional experiments are required to determine the mechanism by which CLVs inhibit the growth of S. scleotiorum.